2016
DOI: 10.1103/physrevd.93.045034
|View full text |Cite
|
Sign up to set email alerts
|

Role of momentum and velocity for radiating electrons

Abstract: This version is available at https://strathprints.strath.ac.uk/55486/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…These developments have motivated various theoretical works devoted to the treatment of radiation reaction in both classical electrodynamics [20][21][22][23][24][25][26], and QED [27][28][29][30][31][32] (see also Ref. [3] for a review).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These developments have motivated various theoretical works devoted to the treatment of radiation reaction in both classical electrodynamics [20][21][22][23][24][25][26], and QED [27][28][29][30][31][32] (see also Ref. [3] for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic plasma simulations have demonstrated that it can alter the physical nature of radiationdominated relativistic current sheets at ultra-high magnetization [17]. Its importance was also demonstrated for the interpretation and modeling of gamma-ray flares in the Crab-Nebulae [18] and of pulsars [19].These developments have motivated various theoretical works devoted to the treatment of radiation reaction in both classical electrodynamics [20][21][22][23][24][25][26], and QED [27][28][29][30][31][32] (see also Ref.[3] for a review). Radiation reaction, treated either using a radiation friction force in the framework of classical electrodynamics or a Monte-Carlo procedure to account for the quantum process of high-energy photon emission, has also recently been implemented in various kinetic simulation codes, in particular Particle-In-Cell (PIC) codes [4][5][6][33][34][35].…”
mentioning
confidence: 99%
“…However it is well known that the so-called Lorentz-Abraham-Dirac (LAD) equation suffers from anomalies, leading to unphysical solutions. Detailed discussions comparing models are given in references 47 , 48 . In order to account for the RR force, we consider the Landau Lifshitz equation 34 .…”
Section: Methodsmentioning
confidence: 99%
“…Until recently, this has been a matter of purely theoretical concern, as under most experimental conditions the self-force represented a negligible correction to any applied forces. Rapid advances in laser technology have changed this situation [2], and the prospect of experimentally accessing regimes where the self-force is not only non-negligible, but actually dominates the dynamics, has rejuvinated interest in understanding its fundamental properties [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the Sokolov model of the self-force[26], the particle can only lose energy in an electrostatic field, regardless of whether or not it is ultra-relativistic[7].…”
mentioning
confidence: 99%